Response to desmopressin is strongly dependent on F8 gene mutation type in mild and moderate haemophilia A - Stoof, Sara C. M.; Sanders, Yvonne V.; Petrij, Fred; Cnossen, Marjon H.; de Maat, Moniek P. M.; Leebeek, Frank W. G.; Kruip, Marieke J. H. A. (Thrombosis and Haemostasis, 2013)
Desmopressin causes two- to six-fold increase of factor VIII (FVIII) in mild or moderate haemophilia A patients. However, responses are variable and little is known whether this is associated with F8 gene mutation. The study objective was to assess the relationship between F8 gene mutation and desmopressin response in haemophilia A patients. Desmopressin response (absolute and relative) was determined in 97 hemophilia A patients. Four amino acid changes (Arg2169His, Pro149Arg, Asn637Ser, and Arg612Cys) and a number of other mutations leading to an aberrant FVIII protein or FVIII deficiency were analysed. Patients with Arg2169His showed significantly lower FVIII levels before and after desmopressin compared to all other mutations (p<0.001). Pro149Arg amino acid change showed significantly lower FVIII levels 1 hour after desmopressin compared to all other mutations (p<0.005). An absolute response with FVIII ≥0.50 IU/ml after 1 hour was observed in 41% (9 of 22) of patients with Arg2169His; however, this was not sustainable after 6 hours in any of these subjects. No patients with Pro149Arg mutation (n=6) showed an absolute response with FVIII _0.50 IU/ml. Patients with other mutations showed significantly more complete and partial responses. Relative responses did not differ between mutations. Our study shows that haemophilia A patients with amino acid change Arg2169His or Pro149Arg have a decreased desmopressin response with regard to FVIII levels as compared to other mutations. Our results indicate that response to desmopressin is dependent on the F8 gene mutation type, despite the fact that multiple factors influence the desmopressin response, even within families.
Keywords: Desmopressin; haemophilia A; blood coagulation factor VIII; mutation; sustainment of response